Transferable ionic simulation models from ab initio calculations - Wilson, M (2000)
Extended ionic models are discussed which account for an ion's response to the environment (for example, polarisation or a change in size and shape) and hence introduce a many-body character. Large-scale simulations are shown to be possible within this framework. The development of high level ab initio electronic structure calculations allows for each aspect of the model to be parameterised independently yielding unambiguous parameter sets which maximise transferability. Several aspects of such parameterisations are discussed with an example ceramic, LiAlSiO4 used to demonstrate the procedures. © 2000 Elsevier Science B.V. All rights reserved.